2018
DOI: 10.1111/eos.12559
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐ and time‐dependent effects of triethylene glycol dimethacrylate on the proteome of human THP‐1 monocytes

Abstract: Triethylene glycol dimethacrylate (TEGDMA) is commonly used in polymer resin-based dental materials. This study investigated the molecular mechanisms of TEGDMA toxicity by identifying its time- and dose-dependent effects on the proteome of human THP-1 monocytes. The effects of different concentrations (0.07-5 mM) and exposure times (0-72 h) of TEGDMA on cell viability, proliferation, and morphology were determined using a real-time viability assay, automated cell counting, and electron microscopy, and laid the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…Some authors demonstrated adverse effects depending on the presence of TEGDMA, HEMA, or UDMA [ 32 , 33 , 34 , 35 , 36 , 37 ]. UDMA is a monomer commonly added in dental resin-based dental materials to enhance their viscosity and is considered an alternative to BisGMA in these materials [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors demonstrated adverse effects depending on the presence of TEGDMA, HEMA, or UDMA [ 32 , 33 , 34 , 35 , 36 , 37 ]. UDMA is a monomer commonly added in dental resin-based dental materials to enhance their viscosity and is considered an alternative to BisGMA in these materials [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the higher the degree of polymerization is, the less toxic the biological effects observed would be [10,12]. Some authors demonstrated adverse effects depending on the presence of TEGDMA, HEMA, or UDMA [32][33][34][35][36][37]. UDMA is a monomer commonly added in dental resin-based dental materials to enhance their viscosity and is considered an alternative to BisGMA in these materials [1,2].…”
Section: Other Types Of Monomersmentioning
confidence: 99%
“…Relatively high cytotoxicity of C was not linked to relevant growth inhibition, while E, and to a lesser extent F, exerted significant antiproliferative effects, but only limited cytotoxicity. Antiproliferative action of methacrylates was also described in human gingival fibroblasts [ 32 , 33 , 34 ], and this effect should be taken into account while testing resin cytotoxicity in cell lines. Published data emphasize inconsistent results of MTT and LDH-release tests in experiments of resin cytotoxicity in human gingival fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In this experimental design, pulp cells were exposed to 0.1, 0.2, and 0.75 mM TEGDMA solution for 24 h. Exposure time and concentrations were chosen due to the substantial cell death which was seen for all treated populations after 48 h and above concentrations of 0.75 mM in our pilot studies. Regarding the employed concentration and study time-frame, similar exposure conditions were used also in other studies to detect gene expression changes and production of specific proteins, all of which yielded representative findings [ 28 , 35 ].…”
Section: Discussionmentioning
confidence: 99%